Predicting Visual Outcomes for Macula-Off Rhegmatogenous Retinal Detachment with Optical Coherence Tomography - Noriyuki Suzuki; Hiroshi Kunikata; Naoko Aizawa; Toshiaki Abe; Toru Nakazawa (Journal of Ophthalmology)
Purpose. We evaluated the ability of novel optical coherence tomography (OCT) parameters to predict postoperative best-corrected visual acuity (BCVA) in macula-off rhegmatogenous retinal detachment (RRD) eyes. Methods. We reviewed the medical records of 56 consecutive eyes with macula-off RRD. Clinical findings were analyzed including the relationship between preoperative OCT findings and 6-month postoperative BCVA. Results. Six-month postoperative BCVA was significantly correlated with preoperative findings including retinal height at the fovea, total and inner layer cross-sectional macular area within 2 mm of the fovea, and preoperative BCVA (P<0.001,P<0.001,P=0.001, and P<0.001, resp.). Multiple regression analysis revealed that the duration of macular detachment and total cross-sectional macular area were independent factors predicting 6-month postoperative BCVA (P=0.024 and P=0.041, resp.). Conclusions. Measuring preoperative total cross-sectional area of the macular layer within 2 mm of the fovea with OCT is a useful and objective way to predict postoperative visual outcome in eyes with macula-off RRD.